Tinjauan Teologis tentang Penerapan Pelayanan Diakonia pada Perayaan Pangkahingisam di Gereja Toraja Mamasa Jemaat Rante Klasis Salumokanan - Neneng Andriani; Soviyanti Bura; Febrianto Randan Parinding (CARAKA: Jurnal Teologi Biblika dan Praktika, 2023)
The author raised this article because he saw that the problem of implementing diakonia services at the pangkahingisam celebration was that it was no longer in accordance with the real concept of pangkahingisam, namely providing diakonia services for congregation members who do not have land, and caring for each other. The purpose of this research is to provide an explanation to congregation members that diakonia services during the Pangkahingisam celebration are very important so that all congregation members feel shared prosperity when the harvest arrives, both those who have land and those who do not. The author uses qualitative research methods through literature study, observation and interviews. The data analysis used is data reduction, data presentation and interpretation. The conclusion of this research shows that the implementation of diakonia services at the Pengkahingisam celebration in the Rante Congregation has not been carried out well, so the congregation members need to review the actual concept of pangkahingam, especially in the concept of diakonia services.